Back Cover: Wavy channel thin film transistor architecture for area efficient, high performance and low power displays (Phys. Status Solidi RRL 3/2014). Issue 3 (March 2014) - Hanna, Amir N.; Torres Sevilla, Galo A.; Ghoneim, Mohamed T.; Hussain, Aftab M.; Bahabry, Rabab R.; Syed, Ahad; Hussain, Muhammad M.
<x xml:space="preserve">Abstract</x> As shown by Hanna et al. (pp. 248–251), by generating a wavy architecture in classical transistor topology, high output current is achieved – opening up bold futuristic opportunity for ultra‐high resolution bright display. Irrespective of the material choice – the unique architecture can provide exciting thin film transistor performance enhancement.Hanna et al. demonstrate the advantage of using the wavy architecture in terms of area efficiency, higher output current, higher field‐effect mobility and similar OFF current levels and Ion/Ioff ratios compared to the planar counterparts for a thin film transistor fabricated with zinc oxide channel material. The low OFF current levels and high Ion/Ioff ratios for the wavy‐channel devices ensure that standby power consumption remains similar to the planar counterparts, while improving the ON current values. This proves the significance of this new architecture for large‐area high‐resolution display applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>